Satia Orange, Children's Librarian, with policeman and horse. - Unknown (Forsyth County Public Library, 1980)
Photo made in the 1980s.
Satia Orange, Children's Librarian, with policeman and horse. Photo made in Winston Square Park.
Keywords: Forsyth County (N.C.) -- History -- Sources; Digital Forsyth; Forsyth County (N.C.) -- History -- Pictorial works